Yield and stover quality of brown mid-rib mutations in different genetic backgrounds of sorghum - UMAKANTH, A V; BHAT, B VENKATESH; BLÃœMMEL, MICHAEL; ARUNA, C; SEETHARAMA, N; PATIL, J V (The Indian Journal of Animal Sciences, 2014)
Genetic control of the lignification process through use of brown mid-rib (bmr) mutations has offered the most direct and productive approach to reducing lignin concentration and increasing digestibility of sorghums. Brown mid- rib genes were introgressed from IS 21888 (bmr-3) and IS 21891(bmr-8) into elite sorghum lines and the advanced progenies were evaluated in relation to normal sorghums. The bmr types were significantly early to flower and mature compared to normal sorghum. Normal sorghum had a significant superiority of 11 and 9% for panicle length and panicle width as compared to bmr sorghum. The bmr types recorded significantly lower grain yield than normal sorghum. However, among the bmr sorghums, CSV 15 × IS 21891 (bmr-8 mutation) derivative recorded a significant superiority over other bmr entries and was at par with the normal sorghum check CSV 20. For stover yields, normal sorghums were significantly superior to the bmr sorghums by 46%. Dry matter intake (DMI) was positively correlated with ME and IVOMD in normal sorghum. However, the correlation of DMI with IVOMD was not significant in bmr sorghums. In both the sorghums, IVOMD was positively correlated with TDN, relative feed value RFV, ME and negatively correlated with ADF and NDF. However, the association of IVOMD with NDF was non-significant in bmr sorghum. The findings of the present study indicated that bmr 3 and bmr 8 genes significantly improved the stover digestibility in specific genetic backgrounds and their interaction with recipient genetic background was evident.